PMO-080 Home enteral tube feeding via percutaneous jejunostomy: a 5-year UK regional study of trends and outcomes. (28th May 2012) - Eyles, L; Henderson, K; Mackel, J; McLean, R
Abstract : Introduction: NHS Lothian home enteral tube feeding (HETF) point prevalence figures reveal that of the 328 adults on HETF in the Lothian region, 18 (5.4%) are being fed via jejunostomy. The aims of this study were to establish the trends in jejunostomy feeding over a 5-year period and to identify the associated complications. Methods: A retrospective review of the regional HETF database was carried out to identify all adults discharged home to the Lothian region on jejunal feeding between 01 January 2007 and 31 December 2011. Results: Ninety adults were discharged on jejunal feeding within the study period. The number of adults receiving jejunostomy feeding at home had increased with an average of 11 per year from 2007 to 2009 rising to an average of 28 per year from 2010 to 2011. Patient age at start of feeding ranged from 17 years old to 79 years old with a median age of 61.6. The most common reason for home jejunal feeding was post-oesophagectomy for oesophageal cancer (65%), followed by gastrectomy (8%) and oesophageal rupture (6%). Length of time on home jejunal feeding ranged from 7 days to 999 days with an average of 165 days, equivalent to 23.6 weeks. The most common clinical outcome was discontinuation of HETF and a return to normal oral diet (64%), 16% died due to underlying disease, and 14% continued on jejunostomy feeding. A review of the complications associated with use of a jejunostomy feeding tube revealed that 55% had documented complications and of this number, 36% had more than one complication documented. In practice, this incidence may be higher as not all patient records had tube site examination documented. A summary of the most common jejunostomy-related complications is shown in the Abstract PMO-080 table 1 below. Conclusion: This study has shown that the number of patients discharged home on jejunostomy feeding over a 5-year period has increased significantly. Average length of time on jejunostomy feeding was almost 6 months therefore the availability of ongoing and timely follow-up in the community is essential. Of particular note is the high rate of tube-related complications, some of which required admission to hospital or treatment at specialist clinics. This incidence could be reduced by improving training and information on prevention and early detection of complications for community based health care professionals as well as for patients. These findings have direct implications for practice in highlighting the need for dedicated, specialist and individualised care for patients at home on jejunostomy feeding. Competing interests: None declared.